ANALISIS LOYALITAS PELANGGAN YANG DIPENGARUHI OLEH EXPERIENTIAL MARKETING DIMEDIASI KEPUASAN PELANGGAN DAN DIMODERASI HARGA PADA GENERASI MILLENNIAL - Pratama, GIlang (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Along with the increasing industrial growth and increased competitiveness among actors in it, encourage companies to formulate marketing strategies that can integrate emotional elements, logic, and general thought processes to connect the company with its customers. Integrated marketing strategy aims to build relationships in such a way that consumers respond to product offerings based on the level of emotional and rational responses as well as create customer satisfaction and build customer loyalty. As a theoretical foundation and an applied solution to the problems that exist, this research is the best way to better understand how the implementation of experiential marketing. This study is a developmental study focusing on the millennial generation of capital as the research object, structural equation modeling method used in analysis phase to describe the relationship between variables studied to produce a conclusion that experiential marketing can influence customer satisfaction in the millennial generation in Indonesia. With the limitations of this research, it is explain that the results give proving scientific studies in Indonesia, especially in the field of marketing.Keywords:Â experiential marketing, customer satisfaction, loyalty, the millennials